Можливі молекулярні механізми мінливості гліадинових генів в інтрогресивних лініях пшениці - Михайлик, С.Ю.; Антонюк, М.З.; Терновська, Т.К. (Фактори експериментальної еволюції організмів, 2014)
Aims. To determine whether phenotypic variability in gliadin spectra of introgression lines was caused by changes in DNA sequences of Gli genes. Methods. PCR using primers specific to Gli genes and retrotransposon. Sequence of PCR products and results alignment comparison. Results. Polymorphism in nucleotide sequences of three Gli genes encoding proteins in α-, β-and ω-zone of spectrum was identified. The alterations include deletions, insertions and single nucleotide transitions and transversions. The mobility of Sukkula retrotransposon relatively to microsatellite (CT)₉G was shown. Conclusions. The gliadin electrophoretic spectra variability is based on changes in the nucleotide sequences of Gli genes such as deletions, insertions and single nucleotide substitutions.

Key words: gliadin, wheat introgression line, gene microsatellite, retrotransposon.